Fumagillin control of Nosema ceranae (Microsporidia: Nosematidae) infection in honey bee (Hymenoptera: Apidae) colonies in Argentina - Giacobino, Agostina (2016)
Information on the long-term consequences of Nosema ceranae to honey bee lifespan and effectiveness of Nosema control with fumagillin is scarce and not always consistent. Our objective in this study was to evaluate the effectiveness of the antibiotic fumagillin to control N. ceranae in hives in East-Central Argentina. Honey bee hives were assigned to 3 experimental treatments, a control group with un-treated hives, a preventive strategy group with hives treated monthly, and a monitoring strategy group with hives treated according to a N. ceranae threshold level. Apiaries were monitored monthly during Fall-Winter 2009 and 2010 and N. ceranae spore intensity and honey bee colony strength measures were estimated. Fumagillin-treated colonies had reduced N. ceranae spores load in 2010 compared to control colonies. However, there was no significant difference between treated and control groups for colony strength measures including adult bee population, bee brood availability, honey, or pollen. Fumagillin treatment reduced N. ceranae intensities but had little effect on colonies. The bee population during Winter was reduced in treated as well as in control colonies. Our results clarify that fumagillin treatment should be at least reviewed and that further research should be conducted to acquire a more complete perspective of Nosemosis disease.